Fundamentals of geophysics - Lowrie, William, 1939- (Cambridge University Press, 2007)
A second edition of this classic textbook on fundamental principles of geophysics for geoscience undergraduates.
Previous edition: 1997.
Keywords: Geophysics.; elektronické knihy; electronic books